Formulación del plan estratégico de la dirección del ambiente 2016 – 2025 del gobierno autónomo descentralizado de la provincia de Cotopaxi - Vilcacundo Chiliquinga, Luis Rodrigo (2016)
The objective of the research was the formulation of the strategic plan 2016-2025 for the Gobierno Autónomo Descentralizado de la Provincia de Cotopaxi, where started reviewing and analyzing the files raised within the constitutional and legal framework in the direction of the environment, the methodology applied was to collect and analysis of documents, using index cards and highlighting of each of them. Each of the functions and processes that address defined, 19 competencies were identified for environmental accreditation quality unit, 13 responsibilities for natural resources and training and unit 11 competencies for the environmental regularization drive. The same methodology and instrument determined be models of environmental management that have been assigned to the address, in compliance with the COOTAD and PDyOT 2025 of the GADPC. In addition working meetings were developed at different times with units’ technicians and authorities of the institution. The information collected was articulated to goal 7 of the National Plan for good living 2013-2017.